Әливтің «Сейілдеу» (1984) атты шығармасы (Journal of Philosophy, Culture and Political Science, 2018)
In the article are considered the comparative interpretations Dulat Aliev’s picture “Picnic” (1984) and Ieronim Bosh’s picture “The ship of fools” (1490) from the positions of phenomenological method and in the context of the European phenomenons “mildred” and “brainstorm”.